Domestic Elder Abuse in Rural Area of Dezful, Iran and Its Relation With Their Quality of Life - Leila Mohebbi; Shahla Zahednejad; Sheida Javadi Pour; Azadeh Saki (Sālmand, 2016)
Objectives: Elderly people are the most vulnerable group of the society and elder abuse phenomenon is one of the most considerable challenges in the field of protecting and caring the elders. The present study was conducted in order to determine domestic elder abuse in rural area of Dezful City, Iran, and its relation with their quality of life in 2013. Methods & Materials: The present study is a correlational cross-sectional study. By cluster random sampling method, 210 elders, aged ≥60 years and resident of Dezful City, were selected to participate in the study. Those elders, who had no cognitive disorder based on Persian version of short test of cognitive status, were entered into the study after obtaining their consent. Afterwards, the questionnaire of family elder abuse; Persian version of SF-36 questionnaire for measuring life quality from health perspective; and also questionnaire of demographic and personal information were fulfilled for them. Collected data were analyzed using descriptive statistics, the Chi-square, and t-tests. Results: Results of the present study indicated that 60.5% of studied sample experienced at least one type of abuse. Maximum prevalence of abuse was related to emotional negligence (38.6%) and minimum level to care negligence (7.3%). At the present study, group of elders without experience of abuse had significantly better life quality than others in all 8 aspects of life quality, except for 2 aspects of physical performance and general health (P<0.05). Conclusion: In spite of high emphasis on respecting elders in our culture, the elders experience different types of abuse. Hence, specific consideration and inducing sensitivity in relevant organizations and individuals is required to prevent the long-term consequences and effects of this issue.